Penerapan Model Pembelajaran Project Based Learning (PjBL) Berbantuan Media Komik untuk Meningkatkan Hasil Belajar pada Materi Gaya Gravitasi Siswa Kelas 4 SDN Kauman 1 Malang - Manfa'ati, Niswatul; Restian, Arina; Ismanto, Puguh Hadi (J-SES : Journal of Science, Education and Studies, 2025)
Abstract: This classroom action research aims to improve student learning outcomes on the topic of gravitational force through the implementation of the Project Based Learning (PjBL) model assisted by comic media in class IV SDN Kauman 1 Malang. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through tests, observations, and field notes. The findings showed that students' learning outcomes improved significantly in each cycle. In the pre-cycle, only 42.8% of students reached the minimum completeness criteria (KKM), increasing to 71.4% in cycle I and 89.3% in cycle II. The use of comic media made abstract concepts more concrete and enhanced students’ engagement. The study concludes that PjBL with comic media is effective in improving student learning outcomes in science subjects. Keyword: Classroom action research, comic media, gravitational force, project based learning